Individual differences in risk taking and endogeneous levels of testosterone, estradiol, and cortisol: A systematic literature search and three independent meta-analyses. (July 2018) - Kurath, Jennifer; Mata, Rui
Highlights: We examined the relation between risk taking and endogenous hormone levels. We report meta-analyses for testosterone, estradiol, and cortisol. We found small effects for testosterone ( r  = 0.12) and estradiol ( r  = 0.10). We found no significant effect for cortisol ( r  = −0.01). Abstract: Hormonal levels have been hypothesized to serve as proximal biological mechanisms underlying individual differences in risk taking. We conducted a systematic literature search and independent meta-analyses to assess the link between endogenous testosterone, estradiol, and cortisol levels and risk-taking related constructs (i.e., risk-taking propensity, impulsivity, sensation seeking, novelty seeking). We found small correlations between risk-taking constructs and testosterone (r = 0.12, 95% CI = 0.08, 0.16, 108 effect sizes, k = 49, N = 9112) as well as estradiol (r = 0.10, 95% CI = 0.02, 0.18, 48 effect sizes, k = 17, N = 2900), but not cortisol (r = −0.01, 95% CI = −0.11, 0.09, 60 effect sizes, k = 27, N = 3880). Overall, these results suggest a biological foundation for individual differences in risk taking. We point out some limitations of past studies and make recommendations for future work investigating the hormonal basis of individual differences in risk taking.